2002
DOI: 10.1053/jhep.2002.33066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sho-saiko-to on hepatocarcinogenesis and 8-hydroxy-2'-deoxyguanosine formation

Abstract: Oxidative stress plays an important role in hepatocarcinogenesis. Although Sho-saiko-to (TJ-9), a Japanese herbal medicine which has been recently administered to patients with chronic liver disease in Japan, prevents hepatocarcinogenesis, the mechanism by which TJ-9 protects against cancer development is not fully understood. 8-Hydroxy-2-deoxyguanosine (8-OHdG), a DNA adduct by reactive oxygen species, is known as a parameter of genetic risk for hepatocarcinogenesis. To clarify whether the preventive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 28 publications
0
49
0
3
Order By: Relevance
“…Our findings suggested that HCV related HCC does not exclusively employ steatosis as a precondition; rather, HCV only acts as a "second hit" on the backdrop of chemically induced genetic injury. Given data that DEN can generate reactive oxygen species (ROS) and enhance oxidative stress, [16][17][18][19] it is tempting to speculate that DEN and steatosis, another known cause of ROS, may act in similar manners to predispose hepatocytes to genotoxic injury and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that HCV related HCC does not exclusively employ steatosis as a precondition; rather, HCV only acts as a "second hit" on the backdrop of chemically induced genetic injury. Given data that DEN can generate reactive oxygen species (ROS) and enhance oxidative stress, [16][17][18][19] it is tempting to speculate that DEN and steatosis, another known cause of ROS, may act in similar manners to predispose hepatocytes to genotoxic injury and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…A later prospective, randomized (albeit nonblind) study by Oka et al [410] could elucidate the use of TJ-9 in preventing the development of HCC in patients with cirrhosis, particularly in patients without HBsAg. Successive studies continued to confirm that TJ-9 could protect experimental liver injury caused by D-galactosamine and liver fibrosis by inhibition of lipid peroxide formation in liver cells [411,412].…”
Section: Tertiary Prevention Of Hcv-related Hccmentioning
confidence: 96%
“…Although the mechanism by which Sho-saiko-to protects hepatocytes against liver disease is not fully elucidated, clinical trials have shown its efficacy in patients with chronic hepatitis and liver cirrhosis in Japan, Korea and China. Some plausible actions as an antioxidant have been reported, for example, scavenging free radicals [60,61] and reducing the hepatic level of malondialdehyde, a product of lipid peroxidation [62] . Shiota et al [61] demonstrated that TJ-9 lowered diethylnitrosamine-induced ROS, resulting in reduction of 8-OHdG formation and hepatocarcinogenesis in rats.…”
Section: Sho-saiko-to (Tj-9 Xiao-chai-hu-tang)mentioning
confidence: 99%
“…Some plausible actions as an antioxidant have been reported, for example, scavenging free radicals [60,61] and reducing the hepatic level of malondialdehyde, a product of lipid peroxidation [62] . Shiota et al [61] demonstrated that TJ-9 lowered diethylnitrosamine-induced ROS, resulting in reduction of 8-OHdG formation and hepatocarcinogenesis in rats. A double-blind multicenter trial reported an improvement in AST and ALT values in 116 chronic hepatitis patients treated with TJ-9 for 12 wk [63] .…”
Section: Sho-saiko-to (Tj-9 Xiao-chai-hu-tang)mentioning
confidence: 99%